IDENTIFICATION OF DIGITAL LITERACY AND PROBLEM-SOLVING SKILLS IN BIOLOGY LEARNING ABOUT ENVIRONMENTAL CHANGE AND CONSERVATION MATERIAL AT ADABIAH 2 HIGH SCHOOL, PADANG - Salsabilah, Nadiyah Farhah; Yogica, Relsas (BIOCHEPHY: Journal of Science Education, 2024)
The 21st century is marked by the development of information technology that is integrated into every aspect of life. To effectively utilize information technology, digital literacy and problem-solving skills are essential. This study aims to identify the digital literacy and problem-solving abilities of phase E students at Adabiah 2 High School, Padang. This research is descriptive in nature. The data produced is qualitative, sourced from questionnaires distributed to 65 phase E students at Adabiah 2 High School, Padang. Based on the identification conducted, it can be concluded that phase E students at Adabiah 2 High School are interested in studying the material on environmental change and conservation. However, they still struggle to understand the material, as evidenced by their inability to determine the causes and effects of environmental issues based on the information they receive. Students have utilized technology, specifically internet access, to learn about this material. However, they do not yet fully possess digital literacy skills, as shown by their inability to differentiate and compare the information gathered in efforts to address the problems of environmental change and conservation.